STRATEGI PEMASARAN ROTI DI KING’S BAKERY DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Emy Khikmawati; Meilani Anggraini; Soja Lana Kesuma (Industrika : Jurnal Ilmiah Teknik Industri, 2021)
ABSTRACT Every industry must make gradual improvements in order to be able to compete in the era of globalization. King's Bakery is a home industry that produces bread. The condition of bread marketing in the King's Bakery business has not been maximized. This study aims to determine the order of priority criteria and sub-criteria in the selection of a bread marketing strategy at King's Bakery and which strategy should be chosen by King's Bakery based on the Analytical Hierarchy Process (AHP) method. Analytical Hierarchy Process (AHP) is a method for ranking decision alternatives and selecting the best one with several criteria. The Analytical Hierarchy Process (AHP) develops a numerical value to find a ranking or priority order of various alternatives in solving a problem, based on the extent to which each alternative meets the decision maker's criteria. The results of this study obtained an assessment of the importance of the criteria in the selection of a bread marketing strategy showing the following priority or weighting scale: the first priority was place (0.546), the second and third priorities are products and distribution channels with the same value (0.231), and the fourth priority was the organization (0.104). From the results of the assessment of the level of alternative importance in the selection of bread marketing strategies, the priority scale or weights are as follows: the first priority was strategy A (3.614), the second priority was strategy C (2.366), the third priority was strategy B (2,000). The best bread marketing strategy that can be used as an alternative to improve bread marketing was strategy A, because it has the highest overall weight value. With technological innovation, it will accelerate production and facilitate marketing for the company.